Implikasi Hukum Perjanjian Kerjasama antara Perusahaan dengan Kontraktor: Analisis Kontrak: BIC/LGL-22-007-002 - Rio Sandra; Muhamad Hasan Sebyar (Lembaga Pengembangan Kinerja Dosen, 2024)
Disputes between contractor service user companies and contractor service providers as a result of the contractors who bind themselves in the cooperation agreement cannot carry out their responsibilities properly. contracting work, infrastructure maintenance that is not in accordance with standards, the use of unqualified materials, the indiscipline of contractor workers in complying with work safety and work schedules that are not on time, so that things do not happen during the cooperation contract period, standard, clear and detailed regulations are needed at the beginning of making a cooperation agreement with the contractor in setting work standards, material specifications, and deadlines for work implementation, so that contractor service providers can carry out their responsibilities professionally and on time. That way the contractor service user company is not worried when entering into a cooperation agreement with the contractor service provider. Because the main focus is standards, empirical juridical research also investigates the empirical aspects. This research is used as descriptive research to show the effect of choosing a cooperation contract model, Types and Sources of Data, research data includes research data includes initial data secondary data. Primary data is data collected directly from respondents or informants, including experts and parties who have the competence to be interviewed. In this study, several legal regulations, including government, presidential, and regional regulations, serve as the legal umbrella for cooperation agreements between companies and contractors. It turns out that the various laws still suffer from norm vagueness, norm conflicts, and norm vacuums. This results in various interpretations of practice, which in turn affects various types of regulations. One of the problems that often occurs is about who participates in the joint Contract between the company & contractor, as well as the process of resolving legal disputes.